The role of exosomes in colorectal cancer disease progression and response to therapy. (February 2020) - Bracci, Laura; Lozupone, Francesco; Parolini, Isabella
Highlights: Shuttling of exosome contents through body fluids contributes to CRC development and progression. CRC exosomes reprogram neighboring cells to colonize distant target organs, thus favouring metastasis. Exosomes from tumor cells or non-immune stromal cells contribute to CRC progression by hijacking APCs and effector T cells. Exosomes are promising biomarkers for diagnosis, prognosis and therapy resistance in CRC. Abstract: Colorectal cancer (CRC) is the second leading cause of cancer mortality in both men and women worldwide. Survival of patients is significantly associated with disease stage at diagnosis. Recent studies highlighted a role of exosomes in CRC development and progression, thus raising the interest on these nanosized vesicular structures as possible biomarkers. Exosomes contain a large variety of molecules, including proteins, lipids and nucleic acids, that are exchanged between cells either within tumor microenvironment or at distant sites from the primary tumor, where they prepare a suitable soil for tumor metastases. The present review summarizes the principal effects of exosomes on CRC development, progression, and provides an update of the most recent findings on the use of exosomal molecules as diagnostic, prognostic and predictive biomarkers in CRC.